Violent deaths of media workers associated with conflict in Iraq, 2003–2012 - Collinson, Lucie; Wilson, Nick; Thomson, George (PeerJ, 2014)
Background. The violent deaths of media workers is a critical issue worldwide, especially in areas of political and social instability. Such deaths can be a particular concern as they may undermine the development and functioning of an open and democratic society. Method. Data on the violent deaths of media workers in Iraq for ten years (2003–2012) were systematically collated from five international databases. Analyses included time trends, weapons involved, nationality of the deceased, outcome for perpetrators and location of death. Results. During this ten-year period, there were 199 violent deaths of media workers in Iraq. The annual number increased substantially after the invasion in 2003 (peaking at n = 47 in 2007) and then declined (n = 5 in 2012). The peak years (2006–2007) for these deaths matched the peak years for estimated violent deaths among civilians. Most of the media worker deaths (85%) were Iraqi nationals. Some were killed whilst on assignment in the field (39%) and 28% involved a preceding threat. Common perpetrators of the violence were: political groups (45%), and coalition forces (9%), but the source of the violence was often unknown (29%). None of the perpetrators have subsequently been prosecuted (as of April 2014). For each violent death of a media worker, an average of 3.1 other people were also killed in the same attack (range 0–100 other deaths). Discussion. This analysis highlights the high number of homicides of media workers in Iraq in this conflict period, in addition to the apparently total level of impunity. One of the potential solutions may be establishing a functioning legal system that apprehends offenders and puts them on trial. The relatively high quality of data on violent deaths in this occupational group, suggests that it could act as one sentinel population within a broader surveillance system of societal violence in conflict zones.
Keywords: Media worker; Iraq; Epidemiology; Surveillance; Violent death